(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Issues Even in large-scale research, only a small number of instances of Parkinson’s disease (PD) will be found. This can be especially difficult in analytical investigations when the causes of sickness vary among groups. Furthermore, large populations will be required to test ideas including numerous variables due to the complex nature of Parkinson’s disease. Due to the relative rarity of Parkinson’s disease (PD), screening of a sizable base population is necessary in order to find enough cases for research. In certain situations, health care registries in certain regions or among registered populations can be used to identify cases of Parkinson’s disease. In some situations, PD cases are discovered outside the medical system, for instance by conducting door-to-door surveys.